Deoxycorticosterone Producing Tumor as a Cause of Resistant Hypertension - Saurabh Gupta; Jose Melendez; Apurv Khanna (Case Reports in Medicine)
We describe a young woman with longstanding resistant hypertension. Evaluation for renal artery stenosis and primary aldosteronism was unrevealing. In this setting of a suppressed plasma aldosterone concentration (PAC) and a suppressed plasma renin activity (PRA), a differential diagnosis of a deoxycorticosterone (DOC) producing tumor was entertained. Biochemical and imaging studies confirmed this diagnosis. Rare and novel DOC producing tumors are an important cause of resistant hypertension.